Comprehensive adhesion model based on the surface characteristics of the coal particles. (1st May 2022) - Lin, Fanfei; Shen, Zhongjie; Liang, Qinfeng; Dai, Zhenghua; Xu, Jianliang; Liu, Haifeng
Highlights: A comprehensive model of coal or char particle adhesion has been proposed. Surface characteristics defined by conversion and melting fraction have been modeled. The kinetic parameters have been used as the limiting condition for adhesion. Ash-carbon ratio, temperature and conversion effects on adhesion have been discussed. Abstract: A comprehensive model for the adhesion of coal ash or char particle was established in this study, which includes the particles' properties and slag layer. The physical properties of the particles include their kinetic parameters and surface characteristics. The particle surface characteristics, such as particle ash ratio and melting fraction, play an important role in particle adhesion. A sub-model of adhesion probability, constructed based on particle surface properties, was also introduced as a part of this comprehensive model. The particle adhesion propensity was determined by considering the kinetic energy criterion of the particles. The model was validated using two sets of particle deposition experiments at different temperatures. Discussion of the model shows that, when the particle kinetic energy is within the medium range, more significant than the critical velocity and less than the critical kinetic energy required to overcome viscosity or surface tension, the particle adhesion is determined by the probability corresponding to the surface characteristics. Furthermore, it is found that the adhesion probability increases with ash-carbon ratio and carbon conversion, and exhibits different trends above and below the flow temperature.